Perancangan Sistem Informasi Penjadwalan Appointment pada Soraaya Studio - Anniwarni Nazara; Serniman Lahagu; Jesika Vinatalia Dachi; Wasis Haryono (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The rapid development of information and communication technology has opened up significant opportunities to enhance service efficiency in various fields, including the beauty industry. Soraaya Studio, which offers a range of beauty services, currently still manages appointment scheduling manually. This manual system leads to several challenges, such as difficulties in efficient schedule management, data duplication, recording errors, and disorganization in the service reservation process. Furthermore, communication with customers regarding schedule confirmation becomes less effective. With the increasing number of customers, this manual scheduling system is no longer able to meet the growing complexity of operational needs.To address these issues, a web-based appointment scheduling system has been designed, which is integrated and user-friendly. This system is built using the PHP programming language with a MySQL database and features a responsive interface, making it easily accessible from various devices, including desktops and mobiles. Key functionalities provided include real-time creation, modification, and cancellation of appointments, management of service availability, and automated notifications via email or text messages to customers and studio staff. The implementation of this system aims to improve the accuracy and speed of the scheduling process, reduce manual errors, and facilitate schedule monitoring by management and staff, thereby enabling Soraaya Studio to provide a more professional and satisfying service to its customers.